Defensive Performance Declines in Ultimate Fighting Championship Fighters Following Anterior Cruciate Ligament Reconstruction - Jacob S. Ghahremani, B.A.; Henry W. Dong, B.A.; Tanya Watarastaporn, M.S.; Nala A. Al-Khatib, B.S.; Lafi S. Khalil, M.D.; Nima Mehran, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To evaluate the impact anterior cruciate ligament reconstruction (ACLR) has on strike evasion rates, strike and landing rates, win percentage, and career longevity in Ultimate Fighting Championship (UFC) fighters. Methods: UFC fighters who underwent ACLR from 1993 to 2022 were matched 2:1 with uninjured controls. The percentage of each injured fighter’s career that occurred before ACLR was deemed the “index percentage.” Injured fighter performance pre-/post-ACLR was compared with control metrics pre-/postindex percentage. Results: Of the 82 patients with documented ACL injuries identified, 48 met the inclusion criteria. Of these, 27 returned for more than 2 fights and were paired with 54 controls. UFC fighters demonstrated return-to-sport rates of 81.25% and 56.25% for at least 1 and 2 fights, respectively. On average, it took 411.85 ± 174.73 (range, 165-879) days for fighters to return. All fighters had significantly lower evasion rates against total significant strikes, distance strikes, and head strikes, postindex (P < .05 for each). ACLR fighters had significantly lower submission attempts and evasion rates against clinch strikes, ground strikes, and total strikes, postindex (P < .05 for each). Controls had a significantly lower evasion rate against leg strikes, postindex. Both groups’ win percentages significantly declined (ACLR, P = .001; control, P = .012). No significant difference in total career fights was observed (P = .873). Conclusions: In this study, we found that most UFC fighters who undergo ACLR return to sport for at least 1 fight; however, just over half return for at least 2 fights. There was not a significant difference in career length between fighters who returned to sport following ACLR for at least 2 fights and their controls. Defensive performance, but not offensive performance, declined significantly following ACLR. All fighters demonstrated significant declines in their win percentage as their career progressed, irrespective of ACLR. Level of Evidence: Level III, retrospective comparative study.